SISTEM INFORMASI MANAJEMEN PRODUKSI PADA TOKO KAIN TENUN MOTIVE ID JEPARA BERBASIS WEB - Joko Minardi; Nasikhah, Na’imatun; Noor Azizah (LogicLink, 2024)
At Motive ID, the production management process is still carried out manually, so errors often occur. Difficulties experienced in the production process include the process of determining raw materials, for example, sometimes stock of yarn as the main material in production is difficult to obtain, especially when the price of yarn increases, apart from that, in terms of human resources, there is still a shortage of workers. These problems cause production management to be less effective. Given the problems that occur with Motive ID, the solution to these problems is the Production Management Information System at the Tenun Troso Motive ID Jepara Cloth Store using Web-Based ERP. This solution can consider existing problems such as efficiency and effectiveness in managing the production of goods. The management process can be carried out according to the desired results.